Assessment for a Statewide Rabies Vaccination Requirement for Dogs and Cats in Kansas - Raybern (Stephens), Chelsea (My University, 2011)
Background Rabies is a highly fatal viral zoonosis that contributes to at least 55,000 human deaths annually throughout the world. Any mammal is susceptible to the rabies virus, but there are only a few species that are reservoirs for rabies; in the U.S., wildlife serves as the source of rabies infection. Domestic animals, such as dogs and cats, contract rabies from these reservoirs; therefore, animal vaccination is key in preventing rabies transmission to humans. Vaccination programs have eliminated canine rabies in the U.S., and Kansas currently does not have a statewide rabies vaccination requirement for dogs and cats. This study analyzes the effectiveness of countywide rabies vaccination laws in Kansas to prevent cases of rabies among dogs and cats. Methods An Animal Rabies Vaccination Survey was created using Survey Monkey and sent to all local health departments in Kansas to determine which counties have a rabies vaccination law. Other county agencies were contacted to determine this information if needed. Rabies test data was obtained for all dogs, cats, and ferrets submitted to the Kansas State University Rabies Laboratory for rabies testing from 2006-2010. The address of residence for the animal was geocoded to determine if it resided inside or outside of city limits. Descriptive analyses were performed on the rabies test data and the difference between two independent proportions was calculated. A hypothesis test and 95% confidence interval was used to determine the significance of each comparison. Results From 2006 through 2010, 75% of dogs and 25% of cats that were submitted for rabies testing were vaccinated against rabies in Kansas. In counties that have a rabies vaccination law for dogs, 53.9% of dogs submitted were vaccinated against rabies and 0.5% of dogs tested positive for rabies. In counties that do not have a vaccination law for dogs, 35.2% of submitted dogs were vaccinated and 0.3% of dogs tested positive for rabies. In counties that have a rabies vaccination law for cats, 21.8% of cats submitted were vaccinated against rabies and 1% of cats tested positive for rabies. In counties that do not have a vaccination law for cats, 11.9% of submitted cats were vaccinated and 2.4% of cats tested positive. The geocoded rabies data revealed that 50.8% of submitted dogs and 15.2% of submitted cats that resided within city limits were vaccinated against rabies compared to 24.8% of submitted dogs and 11.5% of submitted cats that resided outside of city limits were vaccinated against rabies. Furthermore, 0.5% of submitted dogs and 1.8% of submitted cats that resided inside city limits tested positive for rabies compared to 2.1% of submitted dogs and 6.5% of submitted cats that resided outside of city limits tested positive for rabies. Conclusions This study shows that among samples submitted to the KSU Rabies Lab, vaccination rates are much higher in dogs than in cats in Kansas. It shows that there are more dogs submitted for rabies testing that are vaccinated against rabies and more rabies-positive dogs in counties with a rabies vaccination law for dogs than in counties with no dog vaccination law. In addition, there are more cats submitted for rabies testing that are vaccinated against rabies and fewer rabies-positive cats in counties with a rabies vaccination law for cats than in counties with no cat vaccination law. The results also show that there are more vaccinated dogs and cats and fewer rabies-positive dogs and cats submitted for rabies testing residing inside city limits when compared to living outside of city limits. A rabies vaccination requirement of all dogs and cats in Kansas would be beneficial in increasing the number of vaccinated animals and reducing the number of rabies-positive domestic animals.
Keywords: Rabies; Vaccination; Kansas; Law; Public Health (0573)